Eye Surface Temperature as a Potential Indicator of Physical Fitness in Ranch Horses - Esteves Trindade, Pedro Henrique [UNESP]; de Camargo Ferraz, Guilherme [UNESP]; Pereira Lima, Maria Lúcia; Negrão, João Alberto; Paranhos da Costa, Mateus J.R. [UNESP] (Elsevier, 2019)
This study aimed to investigate the use of maximum eye surface temperature (EST max ), recorded by infrared thermography, as an indicator of physical fitness in ranch horses. Data collection was carried out with 16 horses by recording six physical fitness biomarkers (EST max , respiratory rate, creatine kinase activity [CK], and concentrations of total serum protein, plasmatic cortisol, and lactate) before and after a regular working day. We also recorded heart rate during the exercise, exercise duration, average velocity, distance traveled, and air temperature and humidity. The variation between the sampling times was compared by using repeated measures ANOVA or Wilcoxon paired test. The t-test was used to compare EST max means of dehydrated and nondehydrated horses. The differences (DIF-) between each variable's sampling times were calculated, and the Spearman's correlation coefficients between DIF-EST max and DIF- of other variables were estimated. A hierarchical cluster analysis was used to classify the horses according to their physical fitness. All biomarkers increased after the workday, and the EST max means of dehydrated and nondehydrated horses did not differ (P <.05). DIF-CK and DIF-EST max were positively correlated (rs = 0.56, P <.05). The cluster analysis defined two groups of horses (LOW and HIGH), with DIF-EST max and DIF-CK differing statistically between them. HIGH horses showed CK higher than 350 U/L, indicating some degree of muscle damage. These results suggest that EST max has potential to predict changes in CK and, thus could be a useful indicator of physical fitness in ranch horses; although, its effectiveness has to be confirmed in future studies.
Keywords: Animal welfare; Creatine kinase activity; Equine; Infrared thermography; Muscle damage